The value of environmental management and green product design within sustainable development and competitive strategies of the companies: An examination of the energy industry - (:unkn) unknown (ACADEMIC JOURNALS, 2011)
In this study, the conceptual background of environmental management and green product design was examined and based on this, the relative importance of these aspects within the competitiveness and sustainable development of the companies in the energy industry was investigated. The analysis of the value and competitive advantages of the green product design and environmental management issues were provided. Finally, based on the examination of the role of environmental management and sustainable development, a strategic development for the relevant green product design and recommendations were provided. With this respect, the study intended to identify the key success factors in the environmental management and green product design for achieving sustainable development and competitiveness within the energy industry.
Keywords: Environmental management; green product; sustainability; competitive strategy; competitiveness; energy industry; renewable resources